2009
DOI: 10.1212/01.wnl.0000333254.84120.f5
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic intracranial hypertension in men

Abstract: Men with idiopathic intracranial hypertension (IIH) are twice as likely as women to develop severe visual loss. Men and women have different symptom profiles, which could represent differences in symptom expression or symptom thresholds between the sexes. Men with IIH likely need to be followed more closely regarding visual function because they may not reliably experience or report other symptoms of increased intracranial pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
143
4
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(162 citation statements)
references
References 35 publications
12
143
4
3
Order By: Relevance
“…[3] However, less has been reported in men than in women. [6] It does not have a specific by headache or papilledema have been reported. In this paper, an IIH case who applied with blurred vision and diplopia, without accompanying headache will be presented.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[3] However, less has been reported in men than in women. [6] It does not have a specific by headache or papilledema have been reported. In this paper, an IIH case who applied with blurred vision and diplopia, without accompanying headache will be presented.…”
Section: Discussionmentioning
confidence: 97%
“…They reported that visual symptoms are more serious compared to women. [6] IIH cases without headaches are rather identified in children. In the publications, PTS cases without headaches has been suggested in the rate of 9-38% Lim and et al, have reported higher, around 29%, PTS patients without headaches compared to other publications.…”
Section: Case Reportmentioning
confidence: 99%
“…Idiopathic intracranial hypertension among young children has been associated with several new etiologies, including recombinant growth hormone and all-trans retinoic acid. 6,12,15,49 The diagnosis of optic nerve involvement is made using automated perimetry and more recently, optical coherence tomography, laser scanning tomography, and spectral Doppler blood flow analysis of the optic nerve head. More modern neuroimaging techniques such as MR imaging, MR venography, and auto-triggeredelliptic-centric-ordered (ATECO) 3D MR venography are being used to evaluate intracranial processes such as venous sinus thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,30,36,37,45 There are several theories proposed to have a direct link between obesity and IIH, through a specific fat distribution in the body or through production of lipokines, while some others have suggested a converse causation with raised ICP actually causing obesity. 3,5,6,12,45 Over the years, venous obstruction has been reported by authors to cause hydrocephalus in babies. These authors include Shulman and Ransohoff, 44 Rosman and Shands, 39 and Bateman et al 3 Likewise, venous outflow obstruction has been implicated in IIH by Karahalios et al, 26 King et al, 27 Owler et al, 32 and Bateman et al 3 With the advent of direct retrograde cerebral venography and venous sinus manometry, as well as studies with simultaneous measurement of CSF pressures, it has been re- ported that CSF pressure can be reduced by relieving a venous sinus obstruction causing venous hypertension of the superior sagittal sinus.…”
Section: 45mentioning
confidence: 99%
“…Although it is mostly described as a disease affecting young overweight women, there is an increasing incidence in overweight men and children, parallelto the rising prevalence of obesity. (1,5,6,7) In Romania, according to the latest statistics, 19.1% of the women aged 18 to 44 years are overweight, which is more than twice the value reported in 1980 when the rate of obesity in the general population was only 8.6%. (8) …”
Section: Epidemiologymentioning
confidence: 92%